(3cJGH GdcJGH (B( (3Ci GdcJGHI hGdEedGA hGdNW (B)s - (3CHh eMeO YHO Gddg Hf LYaQ Hf OQSJhjg GdaShi,J (B347 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO (B: (3gPG cJGH cfG CdafGg ai NdGaI CejQ GdeDefjf GdeYJVO HGddg JCdjakG eNJUQG JfbU CHhGHg hJbUQ aUhdg YeG GMOKg dfG GdQCi s
(3BNQgG (B:s
(3JeJ aUhd HGH eG CdMb HGdgLGA heG jcKQ GSJYeGd GdCOHGA hGdcJGH dg ai CdaGXge hfCJi ajg Ydi CcKQ eG jecf LeYg eeG jMJGL Edjg ajg Ef TGA Gddg Je GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B76s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(100(3b(B) s
Keywords: (3GdeYGQa GdYGeIs